This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given expression can be written as
( b c d + a c d + a b d + a b c ) 7 = ( a b c d ) 7 ( a 1 + b 1 + c 1 + d 1 ) 7
Outside the expansion we have the term a 7 b 7 c 7 d 7 , thus we have to find the coefficient of the term a 2 b 2 c 2 d 1 inside the expansion.
By general multinomial theorem, the expansion can be written as
0 ≤ α , β , γ , δ ≤ 7 ∑ α + β + γ + δ = 7 α ! β ! γ ! δ ! 7 ! ( a 1 ) α ( b 1 ) β ( c 1 ) γ ( d 1 ) δ
Here α = β = γ = 2 and δ = 1 .
Thus the required coefficient is ( 2 ! ) 3 7 ! = 6 3 0 .